Imaging human coronary cholesterol/urate crystals with cross-polarized micro-optical coherence tomography - Nishimiya, Kensuke; Sharma, Gargi; Singh, Kanwarpal; Ahsen, Osman O.; Gardecki, Joseph A.; Tearney, Guillermo J. (Frontiers in Cardiovascular Medicine, 2024)
Introduction Birefringent crystals such as monosodium-urate (MSU) and cholesterol crystals (CC) likely contribute to the progression of coronary artery disease (CAD) due to their potential to exacerbate inflammation through inflammatory cytokine activation. Here, we present cross-polarized micro-optical coherence tomography (CP-µOCT) for visualizing individual birefringent crystals in human coronary arteries. Methods and results Human cadaver coronary arteries with a history of CAD with or without gout were dissected for CP-µOCT imaging. Specimens were processed for histological identification of birefringence under polarization light microscopy (PLM). CP-µOCT visualized needle-crystals that appeared as long projections in orthogonal planes, and PLM confirmed that CP-µOCT-delineated needle-crystals demonstrated negative birefringence. The needle-crystals were dissolved after immersion in uricase (p < 0.05), and thus were MSU. CP-µOCT was three-dimensionally volume-rendered for counting MSU and CCs in 79 regions of interest sized [750 (x) × 500 (y) × 400 (z) µm]. Crystal counts were normalized by the total coronary length utilized. The relationship between CP-µOCT-delineated MSU counts and those seen in corresponding histology, and the difference in coronary MSU amongst gout vs. non-gout patients was analyzed. CP-µOCT-delineated MSU counts were significantly correlated with MSU counted by PLM-based histology (R = 0.98, p < 0.01), and with histology-derived intimal thickening (R = 0.51, p < 0.01). MSU and CCs were both significantly greater in gout patients compared with non-gout patients (p < 0.05). Discussion These results demonstrate a significant increase in CP-µOCT-delineated crystals in gout vs. non-gout patients, suggesting that this technology can be used to improve our understanding of crystal-driven coronary pathogenesis.